Analysis of the carbon transport near the growth interface with respect to the rotational speed of the seed crystal during top-seeded solution growth of SiC. (11th November 2016) - Umezaki, Tomonori; Koike, Daiki; Harada, Shunta; Ujihara, Toru
Abstract: One of the most important issues of SiC solution growth is to increase the growth rate. In our previous study, we reported that increasing the rotational speed of the seed crystal is effective for improving the growth rate in top-seeded solution growth. In the present study, we investigated the origin of the growth rate improvement through a continuous fluid dynamics simulation with a full-scale three-dimensional model of the experimental setup for actual growth experiment. The numerical results indicated that the stagnant layer above the growth interface decreased in thickness and the carbon concentration gradient then became steep with an increase in the rotational speed of the seed crystal. The experimental growth rate was proportional to the calculated carbon concentration gradient, which indicates that the carbon diffusion through the stagnant layer is the rate-determining process.